1984
DOI: 10.1038/ki.1984.33
|View full text |Cite
|
Sign up to set email alerts
|

Induction of insulin resistance in normal adipose tissue by uremic human serum

Abstract: An incubation of uremic human serum with normal rat adipose tissue will make the subsequently isolated adipocytes less responsive to insulin. To examine the extent of insulin resistance, we obtained sera from nondiabetic, uremic patients, who had not undergone dialysis therapy. The sera were then dialyzed (3500 molecular-weight cutoff) for 18 hr against a defined culture medium to eliminate possible in vitro effects of altered levels of end-product metabolites, electrolytes, and metabolic substrates. After an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

1985
1985
1993
1993

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Amongst these is insulin resistance [6], which has been characterized at the postreceptor level, and also reduced activities of lipoprotein lipase [7] and hepatic triglyceride lipase. A reduction in the ability of insulin to stimulate hexose uptake by uraemic rat adipo cytes has been found [8], and also uraemic human serum can induce an insulin-resistant state in normal rat adipo cytes [9]. These findings, together with the observatioi that glucose utilization in uraemic man is improved by dialysis therapy [10], suggest that uraemia per se is an important factor in the genesis of the reduction in body fat found in the subtotally nephrectomized animals.…”
Section: Discussionsupporting
confidence: 52%
“…Amongst these is insulin resistance [6], which has been characterized at the postreceptor level, and also reduced activities of lipoprotein lipase [7] and hepatic triglyceride lipase. A reduction in the ability of insulin to stimulate hexose uptake by uraemic rat adipo cytes has been found [8], and also uraemic human serum can induce an insulin-resistant state in normal rat adipo cytes [9]. These findings, together with the observatioi that glucose utilization in uraemic man is improved by dialysis therapy [10], suggest that uraemia per se is an important factor in the genesis of the reduction in body fat found in the subtotally nephrectomized animals.…”
Section: Discussionsupporting
confidence: 52%
“…It has been suggested that the mechanism may be related to the presence of an antiinsulin peptide in uremic serum that is dialyzable (22,23). Because, as pointed out previously, chiro-inositol increased in the urine of patients with renal disease who are not diabetic (1), a renal defect alone is unlikely to explain either the widespread deficiency of chiro-inositol mediator in the tissues examined or the differences in pH 2.0 mediator bioactivity seen in the dialysates.…”
Section: Methodsmentioning
confidence: 91%
“…In fact, it has been reported that epididymal fat pads from uremic rats can recover from an insu lin-resistant state when cultured for 20 h in a normal medium [42]. In addition, incubation of uremic serum with normal rat adipose tissue induces insulin resistance [43] and sera from uremic patients inhibit basal utiliza tion of glucose by muscle and erythrocytes [44][45][46].…”
Section: Discussionmentioning
confidence: 99%